Intracerebral Hemorrhage as the Initial Presentation of Chronic Myeloid Leukemia: A Case Report and Review of the Literature - Wang, Huafeng; Cao, Fei; Li, Jianhu; Sun, Ke; Jin, Jie; Wang, Ming (Frontiers in Neurology, 2020)
Intracerebral hemorrhage (ICH) is an unusual complication in chronic myeloid leukemia (CML). Intracranial involvement, causing ICH as an initial presentation is extremely rare in CML. Herein, we reported the first case of a newly diagnosed CML patient, who presented with headaches accompanied by nausea and vomiting as the initial presentations, caused by ICH. He underwent an emergency craniotomy twice and the postoperative pathologic examination confirmed intracranial CML involvement. Interestingly, his bone marrow and cerebrospinal fluid (CSF) smear and pathological study of the involved brain tissue showed proliferation of granulocytes, which were comprised mainly of metamyelocytes and myelocytes, without any blast within the brain tissue, suggesting the stage of CML was in the chronic phase (CP). He then received dasatinib treatment and achieved complete hematologic remission in the first 3-month follow-up but failed to reach a molecular response in the 6-month follow-up. By reporting this case and reviewing relevant references, we suggested intracranial CML involvement should be considered as a potential pathogenesis of ICH when the patient presents with hyperleukocytosis. A craniotomy is mainly for intracranial decompression and benefits the diagnosis of intracranial CML involvement. Tyrosine kinase inhibitors are effective in such patients to some extent, but more appropriate treatment strategies should be investigated in further detail.